The effect of dietary chitin on Atlantic salmon (Salmo salar) chitinase activity, gene expression, and microbial composition - Matilde Mengkrog Holen; Simen Rød Sandve; Thomas Nelson Harvey; Yang Jin; Inga Leena Angell; Knut Rudi; Matthew Peter Kent (Aquaculture and Fisheries)
Chitin is a common component in the natural diet of many fish. While a range of chitin-degrading chitinases have been identified, it is unclear whether chitin is metabolized in fish. Here we use a combination of chitinase activity assays, transcriptomics, and 16S rRNA bacterial analysis to assess the effect of chitin supplementation on Atlantic salmon gene expression and microbial community composition. Atlantic salmon express multiple genes associated with chitin metabolism. We show that the expression and activity of Atlantic salmon chitinases are not affected by the addition of dietary chitin, but we demonstrate an association between gut microbial composition, chitinase activity in the gut, and host chitinase expression. These results contribute to a greater understanding of chitin metabolism in fish.